2014
DOI: 10.1016/j.ejvs.2014.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Venous Reflux in the General Population: Edinburgh Vein Study

Abstract: For every year of follow-up, around 1% of this adult population developed venous reflux. In two thirds of cases, the superficial system was affected. Venous reflux increased the risk of developing varicose veins, especially when combined deep and superficial reflux was present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 32 publications
2
54
1
5
Order By: Relevance
“…In that analysis, the incidence of varicose veins, compared with incidence if there was no reflux, was progressively higher with superficial reflux only and then with combined deep and superficial reflux. 23 Risks related to reflux may begin at an early age; in school children in Bochum, a preclinical refluxing superficial vein led to a 30% risk of trunk varicose veins within 4 years. 24 In contrast to our findings on progression, we found that reflux in the great saphenous vein, at the origin and lower thigh, was particularly important in development of new trunk varices, 23 as also noted in a study comparing reflux in patients with varicose veins and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In that analysis, the incidence of varicose veins, compared with incidence if there was no reflux, was progressively higher with superficial reflux only and then with combined deep and superficial reflux. 23 Risks related to reflux may begin at an early age; in school children in Bochum, a preclinical refluxing superficial vein led to a 30% risk of trunk varicose veins within 4 years. 24 In contrast to our findings on progression, we found that reflux in the great saphenous vein, at the origin and lower thigh, was particularly important in development of new trunk varices, 23 as also noted in a study comparing reflux in patients with varicose veins and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The results vary according to the geographic location and the population being studied [7][8][9]. The Edinburgh Vein Study reported that the prevalence of all categories of varicose veins and CVI increased with age (p < 0.001), while no relation was found with social class [15]. The same study investigated the lifestyle risk factors in another paper.…”
Section: Discussionmentioning
confidence: 99%
“…Vein Study showed that the prevalence of all categories of varicose veins and CVI increased with age (p< 0.001), while no relation was found with social class [15]. It was also reported that obesity, previous pregnancy, lower use of oral contraceptive pills, mobility at work may be implicated in venous reflux in women [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CVI includes varicose veins, post-thrombotic syndrome, primary venous insufficiency, and compression syndromes. This disease characterized by a high prevalence of up to 42% among women and 18% among men [1]. Treatment should be complex and include compression techniques, conservative, and surgical methods.…”
Section: Introductionmentioning
confidence: 99%